Ruko sebagai perwujudan permukiman kaitannya dengan Agenda 21 dan kebijakan nasional (Studi kasus: Ruko Jalan Arjuno Surabaya) - Pindo Tutuko (University of Merdeka Malang, 2003)
The expansion of national and international urban markets for agriculture created turmoil in the rural economy. Agricultural areas are being pulled into the orbit of the urban economy, turning villagers into cash farmers Availability of labor-saving modern agricultural machinery resulting in reduced rural employment Changes in the dynamics of rural-urban relations contribute to the flow of people with dreams of succeeding in cities More complete An urbanization, the more certain its freedom from natural obstacles, the more the city develops as a free entity (a unit that is born), the more fatal the consequences for the region that dominates it.